Impact of Inflation on Purchasing Decisions of Residents of Selected Polish Voivodeships - Wiercioch, Magdalena (Journal of Finance and Financial Law, 2024)
The purpose of the article. The study aimed to assess the impact of an inflation level on purchasing decisions of consumers in selected voivodeships (mazowieckie, lubelskie, podkarpackie, małopolskie). The following hypotheses were adopted: H1: Poles' purchasing decisions in a period of rising inflation depend on the voivodeship in which they live. H1a: Residents of voivodeships with a lower average gross salary (podkarpackie and lubelskie) pay more attention to product features, discounts and places where they shop than residents of voivodeships with a high average gross salary (mazowieckie and małopolskie). H2: Poles' purchasing decisions in a period of rising inflation depend on gender. H2a: Women pay more attention to product features, discounts and places where they shop than men. Methodology. The study employed the diagnostic survey method using an online survey. The voivodeships selected for the study were categorized based on the indicators of an average monthly gross salary in relation to the national average. For mazowieckie and małopolskie voivodeships these values were above 100%, while for podkarpackie and lubelskie voivodeships they ranged from 84–88%. In addition, statistical analyzes were performed to observe relationships such as gender and voivodeship: the chi-square test with an in-depth analysis of standardized categorized residuals, Cramer's V coefficient and Spearman's rank correlation coefficient. Results of the research. The article showed that the relationship between inflation and purchasing behavior of Polish people is an important topic that helps understand how consumers react to rising prices and what strategies they choose when shopping during inflation. Relationship between consumer behavior and the voivodeship was confirmed only in two cases related to shopping habits. This leads to the rejection of H1 and H1a hypotheses. The amount of the average monthly gross salary in relation to the national average (podkarpackie, lubelskie) is not a factor that makes Polish people more inclined to pay attention to product features, discounts and places of purchase, compared to residents of voivodeships with a higher average monthly gross salary (mazowieckie and małopolskie). H2 and H2a hypotheses were confirmed with greater accuracy. It has been noticed that purchasing decisions of Polish people depend on gender, and women pay attention to product features such as a price, promotions, and places where they shop more often than men.